Bilateral parotid enlargement as a presenting feature of bulimia nervosa in a post-adolescent male. Issue 819 (January 1994) - Buchanan, J. A.; Fortune, F.
Abstract : An unusual case of bulimia nervosa in a post-adolescent male is reported. The clinical presentation was one of painless parotid swelling of 3 years duration with marked weight loss and underlying metabolic alkalosis. The diagnostic significance of parotid salivary gland swellings is discussed.